Utilization of Palm Kernel Shell in Concrete Mortar (PKSCM) for Sustainable Construction Material - Mohd Anuar, Nur Shazliena; Wan Jusoh , Wan Amizah (Progress in Engineering Application and Technology, 2024)
The use of environmentally friendly materials like straw, sawdust, and palm kernel shell in construction contributes to sustainable building practices. Roofs, crucial for structural integrity and energy efficiency, are made from various materials, including concrete mortar. Concrete mortar, a popular building material, faces technical issues like cracking, durability concerns, and scaling. This study aims to determine the chemical and physical properties of palm kernel shell, to evaluation of optimum proportion based on mechanical properties of concrete mortar palm kernel shell and comparison effectiveness between normal concrete mortar and concrete mortar palm kernel shell. Experimental work consists of chemical, physical and mechanical testing which is, XRF, SEM, water absorption, compressive strength, sound absorption and water-phobic (hydrophobic) test. The percentage of PKS that added in concrete mortar mix design is 0%, 10%, 20%, 30%, 40%. The result of this study shows that the palm kernel shell can be as a replacement materials for aggregates because PKS contains silica in higher value. The optimum proportion of PKS was 5%. The more percent replacement of PKS, it will reduce the strength and increase the water repellency of concrete mortar compared to normal concrete mortar. This study contribute to establish the construction material such as for roof tiles and finishing from sustainable materials like palm kernel shell.